Composite electrolyte and preparation method thereof, electrolyte film and battery

By introducing self-healing polymer materials with dynamic Lewis acid bonds into solid electrolytes, the mechanical strength difference and electrode expansion problems of solid electrolytes in lithium metal and silicon-based anode systems are solved, and higher ions are achieved Conductivity and mechanical flexibility improve the stability and safety of the battery.

CN119419349APending Publication Date: 2025-02-11SHANGHAI TAIRUI LITHIUM BATTERY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411546592.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing solid electrolytes have poor lithium dendrites growth in lithium metal anode systems and volume expansion problems in silicon-based anode systems, resulting in poor mechanical strength, easy cracking or damage, affecting battery performance and safety.

Method used

Using a composite electrolyte, including metal organic frame material, self-healing polymer material and lithium salt, the self-healing polymer material contains dynamic Lewis acid bonds, which interact with lithium salt through dynamic Lewis acid bonds to split the release activity of lithium salt. Lithium ions improve ionic conductivity, and enhance mechanical flexibility and suppress electrode expansion through flexible chain segments and dynamic repair functions.

Benefits of technology

It improves the ionic conductivity and mechanical flexibility of the composite electrolyte, inhibits electrode expansion, and improves the electrochemical stability and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419349A_ABST
    Figure CN119419349A_ABST
Patent Text Reader

Abstract

The invention discloses a composite electrolyte and a preparation method thereof, an electrolyte film and a battery, and relates to the technical field of new energy batteries. The composite electrolyte comprises a metal organic framework material, a self-repairing polymer material and a lithium salt, wherein the self-repairing polymer material contains a dynamic Lewis acid bond. According to the composite electrolyte provided by the invention, the self-repairing polymer material contains a dynamic Lewis acid bond, the Lewis acid bond easily interacts with Lewis basic anions in the lithium salt so as to dissociate the lithium salt, and the self-repairing polymer material can release more active lithium ions by splitting the lithium salt, so that the concentration of the active ions in the composite electrolyte is improved, and the service life of the composite electrolyte is prolonged. Therefore, the ionic conductivity is improved; the self-repairing polymer material has a flexible chain segment, after the self-repairing polymer material is compounded with the metal organic framework material, the mechanical flexibility of the composite electrolyte can be improved, the expansion of an electrode in the working process of the battery can be inhibited through a dynamic repairing function, a voltage window is improved, and the electrochemical stability and the safety performance of the battery are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of new energy batteries, and in particular to a composite electrolyte and a preparation method thereof, an electrolyte film and a battery. Background Art

[0002] The development of high-energy-density and high-safety lithium-based secondary batteries is of great significance for meeting the large-scale energy storage needs of industries such as new energy vehicles. All-solid-state batteries with lithium metal or silicon-based materials as negative electrodes have great prospects in achieving high energy density and improving safety.

[0003] At present, the solid electrolytes in all-solid-state battery systems mainly include polymer solid electrolytes and inorganic ceramic solid electrolytes. Polymer solid electrolytes usually have the advantages of easy processing and good interface contact, but their ionic conductivity at room temperature is low, their mechanical strength is poor, and it is difficult to inhibit the growth of dendrites, which hinders their practical application. Inorganic oxide solid electrolytes have high electrochemical stability, but they have problems such as low room temperature ionic conductivity and poor interface contact with electrodes; inorganic sulfide solid electrolytes have high ionic conductivity and good ductility, but they have problems such as poor stability and release of toxic gases due to side reactions. Existing solid electrolytes all have certain defects, and it is difficult to meet the problems of poor lithium dendrite growth in lithium metal negative electrode systems and volume expansion in silicon-based negative electrode systems.

[0004] Solid electrolytes have poor mechanical strength, and are prone to cracking or breakage, especially under complex deformation or long-term cycling conditions, which can cause battery performance to deteriorate and even lead to serious safety problems. Summary of the invention

[0005] In view of this, the present application provides a composite electrolyte and a preparation method thereof, an electrolyte film and a battery.

[0006] The embodiment of the present application is implemented as follows: the embodiment of the present application provides a composite electrolyte, including a metal organic framework material, a self-healing polymer material and a lithium salt, wherein the self-healing polymer material contains a dynamic Lewis acid bond.

[0007] Optionally, in some embodiments of the present application, the mass ratio of the metal organic framework material, the self-healing polymer material and the lithium salt is (3-20): (75-96): (1-5); and / or

[0008] In the composite electrolyte, the self-healing polymer material is located inside and on the surface of the metal organic framework material.

[0009] Optionally, in some embodiments of the present application, the dynamic Lewis acid bond comprises a dynamic borate ester bond; and / or

[0010] The self-healing polymer material is formed by reacting a self-healing precursor, wherein the self-healing precursor includes a self-healing monomer and an oligomer; and / or

[0011] The lithium salt includes one or more of an organic lithium salt and an inorganic lithium salt.

[0012] Optionally, in some embodiments of the present application, the self-healing monomer includes one or more of boron trioxide, boric acid, 1,4-phenyldiboric acid, 4,4'-biphenyldiboric acid, 2,7-pyrene diboric acid, and 3,5-dimethoxyphenylboric acid; and / or

[0013] The degree of polymerization of the oligomer is 2 to 10; and / or

[0014] The oligomer comprises a hydroxyl-terminated oligomer, and the hydroxyl-terminated oligomer comprises one or more of polyethylene glycol, polytetramethylene glycol, polycaprolactone glycol, polypropylene glycol, and a hydroxyl polyethylene glycol polylactic acid diblock copolymer; and / or

[0015] The molar ratio of the self-healing monomer to the oligomer is (0.5-2):3; and / or

[0016] The organic lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium difluorooxalatoborate, and lithium bis(oxalatoborate); and / or

[0017] The inorganic lithium salt includes one or more of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium difluorophosphate.

[0018] Optionally, in some embodiments of the present application, the metal organic framework material comprises metal ions and organic ligands; and / or

[0019] The metal organic framework material is a defective metal organic framework material; and / or

[0020] The defective metal organic framework material contains a regulator.

[0021] Optionally, in some embodiments of the present application, the metal ions include one or more of magnesium ions, copper ions, nickel ions, cobalt ions, zinc ions, aluminum ions, zirconium ions and chromium ions; and / or

[0022] The organic ligand includes one or more of an aromatic acid ligand and a heteroaromatic ligand; the aromatic acid ligand contains at least two coordination functional groups, the aromatic acid ligand includes an aromatic dicarboxylic acid ligand, and the aromatic dicarboxylic acid ligand includes one or more of 1,4-benzenedicarboxylic acid, 1,3,5-benzenetricarboxylic acid, 1,4-biphenyldicarboxylic acid, and 4,4'-dihydroxybiphenyl-3,3'-dicarboxylic acid; the heteroatom in the heteroaromatic ligand includes a nitrogen atom, and the heteroaromatic ligand includes one or more of imidazole, 1-methylimidazole, and 2-methylimidazole; and / or

[0023] The molar ratio of the metal ion to the organic ligand is (1.5-3):1; and / or

[0024] The regulator includes a monocarboxylic acid compound; the monocarboxylic acid compound includes one or more of formic acid, acetic acid, propionic acid, butyric acid, valeric acid, hexanoic acid, heptanoic acid, trifluoroacetic acid, and benzoic acid.

[0025] Accordingly, the present application also provides a method for preparing a composite electrolyte, comprising the following steps:

[0026] Providing a metal organic framework material, a self-healing precursor and a lithium salt, and mixing them to obtain a mixture;

[0027] The mixture is heated to make the self-repairing precursor react to form a self-repairing polymer material containing dynamic Lewis acid bonds, thereby obtaining a composite electrolyte.

[0028] Optionally, in some embodiments of the present application, the mass ratio of the metal organic framework material, the self-healing precursor and the lithium salt is (3-20): (75-96): (1-5); and / or

[0029] The temperature of heating the mixture is 60° C. to 120° C. and the time is 5 h to 24 h.

[0030] Optionally, in some embodiments of the present application, the method for preparing the metal organic framework material comprises:

[0031] providing metal salts, organic ligands and solvents;

[0032] The metal salt, the organic ligand and the solvent are mixed and reacted to obtain a metal organic framework material.

[0033] Optionally, in some embodiments of the present application, the metal salt includes one or more of magnesium salt, copper salt, nickel salt, cobalt salt, zinc salt, aluminum salt, zirconium salt and chromium salt; and / or

[0034] The anions in the metal salt include one or more of nitrate ions, sulfate ions, halogen ions, and acetate ions; and / or

[0035] The molar ratio of the metal salt to the organic ligand is (1.5-3):1; and / or

[0036] The solvent includes a polar solvent; the polar solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, methanol, ethanol, propanol, ethylene glycol, and acetone; and / or

[0037] After the metal salt, the organic ligand and the solvent are mixed, the molar concentration of the metal salt is 0.1 mol / L to 0.5 mol / L; and / or

[0038] After the metal salt, the organic ligand and the solvent are mixed, the molar concentration of the organic ligand is 0.05 mol / L to 0.3 mol / L; and / or

[0039] The temperature for the reaction of the metal salt, the organic ligand and the solvent is 30° C. to 150° C.; the reaction time is 12 h to 48 h; and / or

[0040] The metal organic framework material is a defective metal organic framework material, and the mixing of the metal salt, the organic ligand and the solvent further comprises: adding a regulator.

[0041] Optionally, in some embodiments of the present application, after the metal salt, the organic ligand and the solvent react, one or more of centrifugation, extraction and vacuum activation treatment are performed in sequence; wherein,

[0042] The centrifugal solvent of the centrifugation includes a polar solvent, and the polar solvent includes one or more of N,N-dimethylformamide, methanol, ethanol, dimethyl sulfoxide, propanol, and ethylene glycol; the centrifugal speed is 5000rpm to 8000rpm; the centrifugal frequency is 5min / time to 8min / time, and the number of times is 3 to 5 times; and / or

[0043] The extraction solvent includes a polar solvent, and the polar solvent includes one or more of methanol and ethanol; the extraction temperature is 100° C. to 150° C.; the extraction time is 1 day to 5 days; and / or

[0044] The vacuum activation temperature is 70°C to 300°C and the time is 1h to 24h. Accordingly, the present application also provides an electrolyte film, the material of which includes the composite electrolyte or the composite electrolyte prepared by the preparation method.

[0045] Correspondingly, an embodiment of the present application also provides a battery, comprising a positive electrode, a negative electrode, and an electrolyte film located between the positive electrode and the negative electrode, wherein the material of the electrolyte film comprises the above-mentioned composite electrolyte, or comprises a composite electrolyte prepared by the above-mentioned preparation method.

[0046] The composite electrolyte provided in the present application, the self-healing polymer material contains dynamic Lewis acid bonds, the Lewis acid group is easy to interact with the Lewis basic anion in the lithium salt, thereby dissociating the lithium salt, and the self-healing polymer material can release more active lithium ions by splitting the lithium salt, thereby increasing the active ion concentration in the composite electrolyte, thereby improving the ionic conductivity; the self-healing polymer material has a flexible segment, and after being composited with the metal organic framework material, it can improve the mechanical flexibility of the composite electrolyte, and can also inhibit the expansion of the battery electrode during operation through the dynamic repair function, increase the voltage window, and further improve the electrochemical stability and safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0048] Figure 1 is a flow chart of a method for preparing a composite electrolyte provided in an embodiment of the present application;

[0049] Figure 2 It is a physical image and a scanning electron microscope plan view of the defective organic framework material provided in Example 1 of the present application;

[0050] Figure 3 is an X-ray diffraction pattern of the defective organic framework material and its monomer provided in Example 1 of the present application;

[0051] Figure 4 It is a physical picture of the electrolyte membrane provided in Example 1 and Comparative Example 2 of the present application;

[0052] Figure 5 It is a cycle performance diagram of the battery provided by Application Example 1 and Application Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0053] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0054] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.

[0055] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0056] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or several", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0057] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0058] The technical solution of this application is as follows:

[0059] In a first aspect, an embodiment of the present application provides a composite electrolyte, which includes a metal organic framework material, a self-healing polymer material and a lithium salt, wherein the self-healing polymer material contains a dynamic Lewis acid bond.

[0060] It should be noted that metal-organic framework materials are a type of highly ordered porous materials formed by metal ions or metal clusters connected to organic ligands through coordination bonds. They have the characteristics of clear structure, high porosity, large specific surface area, diverse components, and easy customization.

[0061] Self-healing polymer materials are smart materials with self-repairing capabilities. After being damaged, they can self-repair through certain mechanisms, thereby restoring or partially restoring their original physical or chemical properties.

[0062] Dynamic Lewis acid bonds refer to chemical bonds that can break and reform under specific conditions, giving materials the ability to self-repair and improving their durability and service life. Lewis acid refers to electrophilic groups.

[0063] The composite electrolyte provided in the present application, the self-healing polymer material contains dynamic Lewis acid bonds, the Lewis acid group is easy to interact with the Lewis basic anion in the lithium salt, thereby dissociating the lithium salt, and the self-healing polymer material can release more active lithium ions by splitting the lithium salt, thereby increasing the active ion concentration in the composite electrolyte, thereby improving the ionic conductivity; the self-healing polymer material has a flexible segment, and after being composited with the metal organic framework material, it can improve the mechanical flexibility of the composite electrolyte, and can also inhibit the expansion of the battery electrode during operation through the dynamic repair function, increase the voltage window, and further improve the electrochemical stability and safety performance of the battery.

[0064] In some embodiments, the Lewis acid bond includes a dynamic borate bond. It should be noted that the borate group is a typical Lewis acid group with strong Lewis acidity. In the composite electrolyte, the borate group can act as a cationic group and interact with the Lewis basic anion of the lithium salt to split the lithium salt to release more active lithium ions. In addition, the self-healing polymer material containing the dynamic borate bond has good self-healing ability, which can effectively improve the mechanical toughness of the composite electrolyte and inhibit electrode expansion.

[0065] In some embodiments, the self-healing polymer material is formed by reacting a self-healing precursor, wherein the self-healing precursor includes a self-healing monomer and an oligomer.

[0066] Furthermore, the self-healing monomer includes one or more of boron trioxide, boric acid, 1,4-phenyldiboric acid, 4,4'-biphenyldiboric acid, 2,7-pyrenediboric acid, and 3,5-dimethoxyphenylboric acid.

[0067] The polymerization degree of the oligomer is 2 to 10, for example, 3, 4, 5, 6, 7, 8, 9, etc. Within the polymerization degree range, the oligomer has stronger fluidity at room temperature, and is easy to dissolve the self-healing monomer and react with it to form a self-healing polymer material.

[0068] The oligomer includes a hydroxyl-terminated oligomer, and the hydroxyl-terminated oligomer includes one or more of polyethylene glycol, polytetramethylene glycol, polycaprolactone glycol, polypropylene glycol, and hydroxyl polyethylene glycol polylactic acid diblock copolymer. The hydroxyl-terminated oligomer provided in the present application can make the self-healing polymer material have good flexibility and ion-conducting properties, and the hydroxyl-terminated oligomer can easily improve the thermal stability and chemical corrosion resistance of the product.

[0069] Specifically, the polymerization degree of the polyethylene glycol may be 4-10.

[0070] The degree of polymerization of the polytetrahydrofuran diol may be 2 to 3.

[0071] The polymerization degree of the polycaprolactone diol may be 2-3.

[0072] The degree of polymerization of the polypropylene glycol may be 4-10.

[0073] In the hydroxy polyethylene glycol polylactic acid diblock copolymer, the polymerization degree of polyethylene glycol may be 2-6, and the polymerization degree of lactide may be 2-5.

[0074] In some embodiments, the molar ratio of the self-repairing monomer to the oligomer is (0.5-2):3, for example, 0.8:3, 1:3, 1.2:3, 1.5:3, 1.8:3 or any range between two ratios, etc. Within the molar ratio range, it is beneficial for the subsequent self-repairing monomer and the oligomer to fully react.

[0075] In some embodiments, the metal organic framework material comprises metal ions and organic ligands. Further, the organic ligands are coordinated and connected to the metal ions.

[0076] In some embodiments, the metal ions include one or more of magnesium ions, copper ions, nickel ions, cobalt ions, zinc ions, aluminum ions, zirconium ions, and chromium ions.

[0077] In some embodiments, the organic ligand includes one or more of aromatic acid ligands and heteroaromatic ligands. The aromatic rings in aromatic acid ligands and the heteroaromatic rings in heteroaromatic ligands have high rigidity, which can improve the stability of metal organic framework materials. It should be noted that aromatic acid ligands refer to compounds containing aromatic structures and carboxyl groups, and substances with aromatic structures include but are not limited to benzene rings, naphthalene rings, etc.; heteroaromatic ligands mainly refer to heterocyclic ligands containing nitrogen ligands, including but not limited to imidazoles, pyridines, carbazoles, etc.

[0078] In some embodiments, the aromatic acid ligand contains at least two coordination functional groups. Further, the coordination functional groups include one or more of -COOH, -CSSH, -NO2, -SO3H, -PO3H. It should be noted that the coordination functional group refers to a functional group containing a coordination atom, and the aromatic acid ligand contains more than two coordination functional groups, which can make the aromatic acid ligand have better coordination ability and polymerization ability.

[0079] In some embodiments, the aromatic acid ligand comprises an aromatic dicarboxylic acid ligand.

[0080] Specifically, the aromatic dicarboxylic acid ligand includes one or more of 1,4-benzenedicarboxylic acid, 1,3,5-benzenetricarboxylic acid, 1,4-biphenyldicarboxylic acid, and 4,4'-dihydroxybiphenyl-3,3'-dicarboxylic acid.

[0081] In some embodiments, the heteroatom in the heteroaromatic ligand comprises a nitrogen atom.

[0082] Specifically, the heteroaromatic ligand includes one or more of imidazole, 1-methylimidazole, and 2-methylimidazole. The imidazole ring in the heteroaromatic ligand contains a nitrogen-containing ligand, which can effectively carry out coordination and polymerization.

[0083] In some embodiments, the molar ratio of the metal ion to the organic ligand is (1.5-3):1, for example, 1.8:1, 2:1, 2.2:1, 2.5:1, 2.8:1 or any range between two ratios. Within the molar ratio range, the organic ligand can be effectively coordinated with the metal ion to form a crystalline porous material with a network structure, and the metal ion can still have active sites to bind the anions in the lithium salt.

[0084] In some embodiments, the metal organic framework material is a defective metal organic framework material. It should be noted that a defective metal organic framework material refers to a material in which defects are introduced by a specific method during the synthesis of the metal organic framework material, thereby changing the physical and chemical properties of the material so that it has specific functions and applications. These defects can be structural incompleteness, and defects can increase the activity of the metal organic framework material.

[0085] Furthermore, the defects of the defective metal organic framework material include organic ligand missing defects.

[0086] In some embodiments, the defective metal-organic framework material contains a regulator. It can be understood that the defective metal-organic framework material can introduce defects in a variety of ways, and the regulator can be used as one of the ways to introduce defects. The regulator can coordinate with the metal ions in the metal-organic framework material to prevent the connection between some metal ions and organic ligands, thereby forming organic ligand missing defects in the structure. The defects make the metal-organic framework material have a large number of open metal cation active sites, which can bind the anions in the split lithium salt through electrostatic forces, so that the lithium ions can migrate rapidly in the composite electrolyte with the help of the segment movement of the self-healing polymer material and the dynamic bond-forming and bond-breaking process, further improving the lithium ion conductivity of the composite electrolyte. In other words, the regulator will replace part of the organic ligands to participate in the formation of the metal-organic framework and become a part of it.

[0087] In some embodiments, the modulator includes a monocarboxylic acid compound.

[0088] Furthermore, the monocarboxylic acid compound includes one or more of formic acid, acetic acid, propionic acid, butyric acid, valeric acid, hexanoic acid, heptanoic acid, trifluoroacetic acid, and benzoic acid.

[0089] In some embodiments, the content of the metal ions is less than the content of the organic ligands. In this way, the organic ligands can promote coordination and polymerization to form metal organic framework materials, and the regulator can effectively regulate the defects of the metal organic framework materials, so that they have a larger specific surface area and pore volume, and promote the self-healing monomers and oligomers to fully enter the skeleton of the metal organic framework materials, and form a more continuous and complete self-healing polymer material after polymerization.

[0090] In some embodiments, in the composite electrolyte, the self-healing polymer material is located inside and on the surface of the metal organic framework material. It can be understood that the metal organic framework material is a porous inorganic-organic hybrid crystalline material with a porous framework structure, the internal holes form an ordered channel, the self-healing polymer material is located in the ordered channel, and is located on the surface of the framework, which can fully ensure that the metal organic framework material is mixed evenly, increase the contact area between the metal organic framework material and the self-healing polymer material, so that the self-healing polymer material can fully improve the mechanical flexibility of the composite electrolyte, and suppress the electrode expansion problem of the solid-state battery during operation through the dynamic repair function, further improving the battery's electrochemical stability and safety performance.

[0091] It should be noted that the self-healing polymer material is formed by in-situ polymerization after the self-healing monomers and oligomers enter the interior and surface of the metal organic framework material.

[0092] In some embodiments, the lithium salt includes one or more of an organic lithium salt and an inorganic lithium salt.

[0093] Furthermore, the organic lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorooxalatoborate (LiDFOB), and lithium bis(oxalatoborate) (LiBOB).

[0094] The inorganic lithium salt includes one or more of lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), and lithium difluorophosphate (LiP2F2).

[0095] In some embodiments, the mass ratio of the metal organic framework material, the self-healing polymer material and the lithium salt is (3-20): (75-96): (1-5), for example, it can be 12:85:3, 10:85:5, 5:92:3, 17:80:3, 7:90:3, 4:95:1, 13:85:2 or any range between two ratios. Within the mass ratio range, the self-healing polymer material can decompose the lithium salt to release more active lithium ions, thereby increasing the concentration of lithium ions in the composite electrolyte; the metal organic framework material has metal cation active sites on its surface, which bind the silver ions in the decomposed lithium salt, so that the lithium ions in the composite electrolyte can migrate rapidly with the help of the segment movement and dynamic bond formation and breaking process of the self-healing polymer material, thereby further improving the lithium ion conductivity of the composite electrolyte; the self-healing polymer material has flexible segments, which are distributed in the ordered channels and framework surface of the metal organic framework material, which can fully improve the flexibility of the composite electrolyte, and effectively inhibit electrode expansion through dynamic repair function, thereby improving the overall performance of the composite electrolyte and the battery.

[0096] Second, see Figure 1 , the embodiment of the present application also provides a method for preparing a composite electrolyte, comprising the following steps;

[0097] S11, providing a metal organic framework material, a self-healing precursor and a lithium salt, and mixing them to obtain a mixture;

[0098] S12, heating the mixture to allow the self-healing precursor to react to form a self-healing polymer material, wherein the self-healing polymer material contains dynamic Lewis acid bonds, thereby obtaining a composite electrolyte.

[0099] The metal organic framework material, the self-healing precursor, the self-healing polymer material and the lithium salt are mentioned above and will not be described in detail here.

[0100] In the S11:

[0101] In some embodiments, the method for preparing the metal organic framework material comprises:

[0102] S111, providing a metal salt, an organic ligand and a solvent;

[0103] S112, mixing the metal salt, the organic ligand and the solvent, and reacting them to obtain a metal organic framework material.

[0104] In some embodiments, the metal salt includes one or more of a magnesium salt, a copper salt, a nickel salt, a cobalt salt, a zinc salt, an aluminum salt, a zirconium salt, and a chromium salt.

[0105] In some embodiments, the anions in the metal salt include one or more of nitrate ions, sulfate ions, halide ions, and acetate ions.

[0106] In some embodiments, the molar ratio of the metal salt to the organic ligand is (1.5-3):1, for example, 1.8:1, 2:1, 2.2:1, 2.5:1, 2.8:1 or any range between two ratios. Within the molar ratio range, the organic ligand can be effectively coordinated and connected with the metal ions in the metal salt to form a crystalline porous material with a network structure.

[0107] In some embodiments, the solvent includes a polar solvent. Further, the polar solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, methanol, ethanol, propanol, ethylene glycol, and acetone.

[0108] In some embodiments, after the metal salt, the organic ligand and the solvent are mixed, the molar concentration of the metal salt is 0.1 mol / L to 0.5 mol / L, for example, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L or a range between any two values, etc. Within the molar concentration range, the metal salt is facilitated to be fully dissolved and dispersed.

[0109] In some embodiments, after the metal salt, the organic ligand and the solvent are mixed, the molar concentration of the organic ligand is 0.05 mol / L to 0.3 mol / L, for example, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L or a range between any two values, etc. Within the molar concentration range, the organic ligand is facilitated to be fully dissolved and dispersed.

[0110] In some embodiments, the metal organic framework material is a defective metal organic framework material, and the mixing of the metal salt, the organic ligand and the solvent further comprises: adding a regulator. It is understood that the regulator is added to form organic ligand defect sites to bind anions in the lithium salt.

[0111] In some embodiments, the mass ratio of the metal salt to the regulator is (2-6):1, for example, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1 or any range between two ratios. Within the mass ratio range, the regulator can effectively adjust the defects of the metal organic framework material, so that it has a larger specific surface area and pore volume, which is conducive to the self-healing monomer to fully enter the skeleton of the metal organic framework material, and form a more continuous and complete self-healing polymer material after polymerization, and the defects formed are conducive to binding the anions in the lithium salt.

[0112] The materials of the regulator are mentioned above and will not be described in detail here.

[0113] It should be noted that the defective metal organic framework material can also be formed by controlling the temperature or time of the reaction.

[0114] In some embodiments, the temperature of the reaction of the metal salt, the organic ligand and the solvent is 30°C to 150°C, for example, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or any range between two values, etc.; the reaction time is 12h to 48h, for example, 15h, 18h, 20h, 22h, 25h, 28h, 30h, 32h, 35h, 38h, 40h, 42h, 45h, 48h or any range between two values, etc. Thus, under the reaction conditions, it is favorable for the metal ions in the metal salt and the organic ligand to undergo a hydrothermal reaction to form a crude metal organic framework material.

[0115] In some embodiments, after the metal salt, the organic ligand and the solvent react, one or more of centrifugation, extraction and vacuum activation treatments are performed sequentially.

[0116] In some embodiments, the centrifugal solvent of the centrifugation includes a polar solvent, and the polar solvent includes one or more of N,N-dimethylformamide, methanol, ethanol, dimethyl sulfoxide, propanol, and ethylene glycol. The speed of the centrifugation is 5000rpm to 8000rpm, for example, it can be 5500rpm, 6000rpm, 6500rpm, 7000rpm, 7500rpm, or a range between any two values. The frequency of the centrifugation is 5min / time to 8min / time, and the number of times is 3 to 5 times, for example, it can be 5.5min / time, 6min / time, 6.5min / time, 7min / time, 7.5min / time, 8min / time, or a range between any two values.

[0117] Thus, under the centrifugal conditions, the obtained crude metal organic framework product can be fully washed and dried.

[0118] In some embodiments, the extraction solvent includes a polar solvent, and the polar solvent includes one or more of methanol and ethanol. The extraction temperature is 100°C to 150°C, for example, 110°C, 120°C, 130°C, 140°C, 150°C, or a range between any two values; the extraction time is 1 day to 5 days, for example, 1.5 days, 2 days, 2.5 days, 3 days, 3.5 days, 4 days, 4.5 days, or a range between any two values.

[0119] It should be noted that during the reaction of the metal salt and the organic ligand, there may be small molecular weight substances, residual metal salts or residual organic ligands, and residual solvents generated by partial incomplete reactions inside or on the surface of the metal organic framework material. Under the extraction conditions, these impurities can be dissolved and removed to improve the purity of the metal organic framework material.

[0120] In some embodiments, the temperature of the vacuum activation is 70°C to 300°C, such as 100°C, 120°C, 150°C, 180°C, 200°C, 220°C, 250°C, 280°C, or any range between two values, etc.; the time is 1h to 24h, such as 2h, 5h, 8h, 10h, 12h, 15h, 18h, 20h, or any range between two values, etc. The vacuum degree of the vacuum activation is less than or equal to 133Pa.

[0121] In this way, under the vacuum activation conditions, it is not only beneficial to further remove the residual solvent molecules and organic ligands in the pores of the metal organic framework material, but also to increase the unsaturated active sites and improve the binding of anions in the split lithium salt.

[0122] In some embodiments, the self-healing precursor includes self-healing monomers and oligomers.

[0123] In some embodiments, the molar ratio of the self-repairing monomer to the oligomer is (0.5-2):3, for example, 0.8:3, 1:3, 1.2:3, 1.5:3, 1.8:3 or any range between two ratios. Within the molar ratio range, it is beneficial for the subsequent self-repairing monomer and the oligomer to fully react, and the oligomer is liquid at room temperature, which is beneficial for fully dissolving and dispersing the self-repairing monomer.

[0124] In some embodiments, the mixing of the metal organic framework material, the self-healing precursor and the lithium salt further includes ball milling.

[0125] Specifically, the rotation speed of the ball mill is 250 r / min to 350 r / min, for example, 280 r / min, 280 r / min, 280 r / min or a range between any two values, etc.; the ball milling time is 0.5 h to 2 h, for example, 0.8 h, 1 h, 1.2 h, 1.5 h, 1.8 h or a range between any two values, etc. Ball milling can promote the full and uniform dispersion of the metal organic framework material, the self-healing precursor and the lithium salt.

[0126] In S12:

[0127] In some embodiments, the mass ratio of the metal organic framework material, the self-healing precursor and the lithium salt is (3-20): (75-96): (1-5), for example, it can be 5:85:3, 10:85:3, 15:85:3, 10:80:3, 10:90:3, 10:95:3, 10:85:2 or any range between two ratios. Within the mass ratio range, it is beneficial for the self-healing precursor to polymerize in situ inside and on the surface of the metal organic framework material to form a self-healing polymer material, and promote the full contact between the lithium salt and the metal organic framework material and the self-healing polymer material, and synergistically improve the ionic conductivity and mechanical flexibility of the composite electrolyte, as well as the stability of the battery.

[0128] In some embodiments, the temperature of heating the mixture is 60°C to 120°C, for example, 70°C, 80°C, 90°C, 100°C, 110°C, or a range between any two values, etc.; the time is 5h to 24h, for example, 8h, 10h, 12h, 15h, 18h, 20h, 22h, or a range between any two values, etc. In this way, under the heating conditions, it is beneficial to promote the formation of the composite electrolyte.

[0129] In some embodiments, the heating of the mixture is performed in an environment with a dew point temperature less than -40°C. It should be noted that the dew point temperature refers to the temperature at which the air is cooled to saturation under the condition that the water vapor content in the air remains unchanged and the air pressure is kept constant. Under the condition of the dew point temperature, it is beneficial to reduce the influence of moisture on the composite electrolyte.

[0130] In a third aspect, an embodiment of the present application further provides an electrolyte film, the material of which includes the above-mentioned composite electrolyte.

[0131] It should be noted that the electrolyte film can be obtained by pouring the mixture in S11 into a mold, coating it into a film, and then performing the heating treatment in S12.

[0132] In some embodiments, the thickness of the electrolyte film is 20 μm to 100 μm, for example, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or a range between any two values.

[0133] In a third aspect, an embodiment of the present application further provides a battery, comprising a positive electrode, a negative electrode, and an electrolyte film located between the positive electrode and the negative electrode, wherein the material of the electrolyte film comprises the above-mentioned composite electrolyte.

[0134] The battery provided in the present application adopts the above-mentioned composite electrolyte as the material of the electrolyte film. The self-healing polymer material contains dynamic Lewis acid bonds, which makes it have a strong ability to dissociate lithium salts. The self-healing polymer material releases active lithium ions by splitting the lithium salts, thereby increasing the active ion concentration in the composite electrolyte and thus improving the ion conductivity. The metal-organic framework material also has a large number of open metal cation active sites, which can bind the anions in the split lithium salts through electrostatic forces, so that the lithium ions can migrate rapidly in the composite electrolyte with the help of the chain segment movement of the self-healing polymer material and the dynamic bond-forming and bond-breaking process, further improving the lithium ion conductivity of the composite electrolyte. The self-healing polymer material also has a flexible segment. After being composited with the metal-organic framework material, it can improve the mechanical flexibility of the composite electrolyte, and can also suppress the expansion of the battery electrode during operation through the dynamic repair function, further improving the electrochemical stability and safety performance of the battery.

[0135] In some embodiments, the positive electrode active material in the positive electrode includes one or more of lithium nickel manganese oxide, lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, and lithium nickel cobalt manganese oxide.

[0136] In some embodiments, the negative electrode includes one or more of a metallic lithium negative electrode, a metallic lithium alloy negative electrode, a graphite negative electrode, a silicon-based negative electrode, a silicon-graphite composite negative electrode, and a copper foil lithium-free negative electrode.

[0137] In some embodiments, the thickness of the negative electrode is 60 μm to 100 μm, for example, 70 μm, 80 μm, 90 μm, or a range between any two values.

[0138] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.

[0139] Example 1

[0140] This embodiment provides a composite electrolyte and an electrolyte film, and the preparation method includes:

[0141] Weigh 4,4'-dihydroxybiphenyl-3,3'-dicarboxylic acid, Mg(NO3)2·9H2O and N,N-dimethylformamide, mix them, stir them magnetically to fully dissolve them, and promote dispersion by ultrasound to obtain a mixed solution; wherein the molar concentration of Mg(NO3)2·9H2O in the mixed solution is 0.35 mol / L, the molar concentration of 4,4'-dihydroxybiphenyl-3,3'-dicarboxylic acid is 0.22 mol / L, and the molar ratio of Mg(NO3)2·9H2O to 4,4'-dihydroxybiphenyl-3,3'-dicarboxylic acid is 1.59:1. According to the mass ratio of formic acid and Mg(NO3)2·9H2O, The ratio of formic acid is 1:4.3, and the formic acid is weighed and dissolved in the above mixed solution. After being fully dissolved, it is transferred to a pressure-resistant reactor, and reacted at 120°C for 24 hours. The obtained initial product is placed in 90°C N,N-dimethylformamide for immersion and suction filtration for 3 times to obtain a filter residue, i.e., a crude metal organic framework product. The crude metal organic framework product is centrifuged at 8000 rpm for 3 times with ethanol, and each centrifugation time is 5 minutes; then, the crude metal organic framework product is extracted with methanol at 100°C for 5 days, and the filter residue is obtained by suction filtration. Finally, the filter residue is activated at 100°C under vacuum for 12 hours to obtain a defective metal organic framework material;

[0142] Polyethylene glycol (number average molecular weight of 400) and boron trioxide were weighed in a container at a molar ratio of 3:1, and magnetic stirring was performed for 6 hours until the boron trioxide was completely dissolved to obtain a self-healing precursor;

[0143] The defective metal organic framework material, the self-healing precursor and lithium bis(trifluoromethanesulfonyl)imide were weighed in a mass ratio of 12:85:3, and a uniformly mixed mixture was obtained by ball milling at a speed of 300 r / min for 1 hour. The mixture was then scraped on a polytetrafluoroethylene plate and heated at 90°C in a vacuum oven for 12 hours for reaction. Boron trioxide and polyethylene glycol reacted inside and on the surface of the defective metal organic framework material to form a self-healing polymer material containing dynamic borate ester bonds. After the reaction was completed and the material was cooled to room temperature, a composite electrolyte was obtained, and an electrolyte film with a thickness of 40 μm was obtained by cold pressing.

[0144] Example 2

[0145] This embodiment is basically the same as Embodiment 1, except that in this embodiment, Mg(NO3)2·9H2O is replaced by Zn(NO3)2·6H2O.

[0146] Example 3

[0147] This embodiment is substantially the same as Embodiment 1, except that in this embodiment, 4,4'-dihydroxybiphenyl-3,3'-dicarboxylic acid is replaced by 2-methylimidazole.

[0148] Example 4

[0149] This embodiment is substantially the same as Embodiment 1, except that in this embodiment, boron trioxide is replaced by 1,4-phenylenediboric acid.

[0150] Example 5

[0151] This embodiment is substantially the same as Embodiment 1, except that polyethylene glycol is replaced by polycaprolactone diol in this embodiment.

[0152] Example 6

[0153] This embodiment is substantially the same as Embodiment 1, except that in this embodiment, lithium bis(trifluoromethanesulfonyl)imide is replaced by lithium hexafluorophosphate.

[0154] Example 7

[0155] This embodiment is substantially the same as embodiment 1, except that in this embodiment, formic acid is replaced by benzoic acid.

[0156] Example 8

[0157] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, the mass ratio of the defective metal organic framework material, the self-healing precursor and lithium bis(trifluoromethanesulfonyl)imide is 1:96:3.

[0158] Example 9

[0159] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, the mass ratio of the defective metal organic framework material, the self-healing precursor and lithium bis(trifluoromethanesulfonyl)imide is 20:75:5.

[0160] Example 10

[0161] This embodiment is substantially the same as Embodiment 1, except that the mass ratio of formic acid to Mg(NO3)2·9H2O in this embodiment is 1:2.

[0162] Embodiment 11

[0163] This embodiment is substantially the same as Embodiment 1, except that the mass ratio of formic acid to Mg(NO3)2·9H2O in this embodiment is 1:6.

[0164] Example 12

[0165] This embodiment is substantially the same as embodiment 1, except that in this embodiment, the temperature at which the mixture is heated in the vacuum oven is 120°C.

[0166] Embodiment 13

[0167] This embodiment is substantially the same as embodiment 1, except that in this embodiment, the temperature at which the mixture is heated in the vacuum oven is 60°C.

[0168] Embodiment 14

[0169] This embodiment is substantially the same as embodiment 1, except that formic acid is not added in this embodiment.

[0170] Comparative Example 1

[0171] This comparative example is basically the same as Example 1, with the only difference being that in this comparative example, no self-healing precursor is prepared, polyethylene glycol with a number average molecular weight of 400 is replaced by polyethylene glycol with a number average molecular weight of 1500, and polyethylene glycol with a number average molecular weight of 1500 and defective metal organic framework material and lithium bis(trifluoromethanesulfonyl)imide are mixed in a mass ratio of 85:12:3.

[0172] Comparative Example 2

[0173] This comparative example is substantially the same as Example 1, except that in this comparative example, no defective metal organic framework material is prepared, and the self-healing precursor and lithium bis(trifluoromethanesulfonyl)imide are mixed in a mass ratio of 90:10.

[0174] Observe the physical image and scanning electron microscope image of the defective organic metal framework material in Example 1. Figure 2 , where (a) is the physical image and (b) is the scanning electron microscope image.

[0175] Depend on Figure 2 It can be seen that the defective organic metal framework material of Example 1 is a kind of light yellow powder material at the macro level, and the defective organic metal framework material has a rod-like structure at the micro level, and the rod-like structure provides good support for the electrolyte film.

[0176] The defective organic metal framework material and the organic ligand therein in Example 1 were subjected to X-ray diffraction test, and the results were as follows: Figure 3 .

[0177] Depend on Figure 3 It can be seen that by comparing with the diffraction pattern of the monomer, it was found that the peaks of the defective organic metal framework material in Example 1 at diffraction angles of 4.69° and 8.26° showed the characteristic peaks of the crystal structure of the defective organic metal framework material, indicating that it does not contain independently existing organic ligands and other impurities and has a high purity.

[0178] Observe the physical pictures of the electrolyte membranes in Example 1 and Comparative Example 2. Figure 3 , wherein (a) is the electrolyte membrane of Comparative Example 2, and (b) is the electrolyte membrane of Example 1.

[0179] Depend on Figure 3 It can be seen that the electrolyte film of Comparative Example 2 is transparent and can transmit light, while the electrolyte film of Example 1 is snow-white and has a highly dense structure, through which light cannot pass, indicating that the electrolyte film of Example 1 has high uniformity and good flexibility and support.

[0180] The electrolyte films of Test Examples 1 to 14 and Comparative Examples 1 to 2 were tested for ion conductivity and voltage window. The results are shown in Table 1.

[0181] Among them, the ionic conductivity was tested at 25°C. The test method included: cutting the electrolyte film into a circle with a diameter of 1.81cm, placing it between two stainless steel electrodes (SS), and assembling it into a SS / solid polymer electrolyte membrane / SS simulated battery for testing. The test frequency range was 1MHz~0.01Hz, and the AC voltage amplitude was 10mV; before the test, the device was heated at 60°C for 2h to ensure sufficient contact between the electrode and the solid polymer electrolyte membrane. The obtained test data was simulated and analyzed using Ziew software.

[0182] The voltage window test method is linear sweep voltammetry. The specific test method includes: cutting the electrolyte film into a circle with a diameter of 1.8 cm, assembling the positive electrode shell, stainless steel electrode (SS), solid electrolyte membrane, lithium metal, stainless steel electrode (SS), and spring SS||solid electrolyte membrane||Li style asymmetric button cell for testing. The voltage is gradually increased from 0V to 5V (relative to Li / Li) at a scan rate of 0.01V / s. + Potential), and record the change of current with voltage during the period. When the voltage gradually increases, if the current increases sharply, it indicates that the solid electrolyte has decomposed at this time.

[0183] Table 1

[0184]

[0185] As can be seen from Table 1, the composite electrolyte provided in the present application includes a lithium salt, a metal organic framework material, and a self-healing polymer material containing a dynamic Lewis acid bond. The Lewis acid group interacts with the Lewis basic anion in the lithium salt, which promotes the lithium salt to release more active lithium ions, and significantly improves the ionic conductivity compared with Comparative Examples 1 to 2. After the self-healing polymer material is composited with the metal organic framework, the mechanical flexibility is improved, and the expansion of the electrode can be suppressed through self-healing, thereby improving the voltage window and electrochemical stability.

[0186] Application Example 1

[0187] This application embodiment provides a battery, and the preparation method includes:

[0188] A battery was assembled with lithium nickel cobalt manganese oxide as the positive electrode and metallic lithium as the negative electrode and the electrolyte film in Example 1, wherein the thickness of the negative electrode was 80 μm.

[0189] Application Examples 2 to 14

[0190] Application Examples 2 to 14 are substantially the same as Application Example 1, with the only difference being that in Application Examples 2 to 14, the electrolyte membrane of Example 1 is replaced by the electrolyte membranes of Examples 2 to 14, respectively.

[0191] Application Comparative Examples 1 to 2

[0192] Application Comparative Examples 1-2 are substantially the same as Application Example 1, except that the electrolyte membrane of Example 1 is replaced by the electrolyte membrane of Comparative Examples 1-2 in Application Comparative Examples 1-2.

[0193] The cycle performance of the batteries of application examples 1 to 14 and application comparative examples 1 to 2 was tested, wherein the capacity retention rate and coulombic efficiency of application example 1 and application comparative example 1 were Figure 5 The rest of the data results are shown in Table 2.

[0194] The cycle test method includes: at 25°C, the battery is charged and discharged for one cycle at 30°C and 2.7V to 3V at a rate of 0.05C for formation, and then the battery is charged and discharged at a rate of 0.1C in the range of 2.7V to .3V for cycle test, and the discharge capacity of the battery in the first week and the discharge capacity after 300 cycles are recorded. The capacity retention rate of 300 weeks = the discharge capacity of 300 weeks / the discharge capacity of the first week*100%.

[0195] Table 2

[0196]

[0197]

[0198] From Table 2 and Figure 5 It can be seen that the coulombic efficiency refers to the ratio of the discharge capacity of the battery to the charging capacity in the same cycle process. A slight difference in coulombic efficiency will have a significant impact on the performance and life of the battery. The average coulombic efficiency of the comparative example 1 is 99.79%, while the average coulombic efficiency of the embodiment 1 is 100.09%, indicating that the attenuation rate of the comparative example 1 is significantly higher than that of the embodiment 1.

[0199] The composite electrolyte provided in the present application is applied to the electrolyte film of the battery, which significantly improves the cycle performance of the battery by increasing the active lithium ion concentration and inhibiting electrode expansion through self-repair. After 300 cycles, the capacity retention rate of the battery in the application example is still above 85%, while the capacity retention rate of the battery in the application comparison examples 1 to 2 is less than 80%. The battery improved in the present application has high electrochemical stability and safety performance.

[0200] The technical solutions provided by the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A composite electrolyte, characterized in that The invention comprises a metal organic framework material, a self-repairing polymer material and a lithium salt, wherein the self-repairing polymer material contains a dynamic Lewis acid bond.

2. The composite electrolyte according to claim 1, characterized in that The mass ratio of the metal organic framework material, the self-healing polymer material and the lithium salt is (3-20): (75-96): (1-5); and / or In the composite electrolyte, the self-healing polymer material is located inside and on the surface of the metal organic framework material.

3. The composite electrolyte according to claim 1, characterized in that The dynamic Lewis acid bond comprises a dynamic borate ester bond; and / or The self-healing polymer material is formed by reacting a self-healing precursor, wherein the self-healing precursor includes a self-healing monomer and an oligomer; and / or The lithium salt includes one or more of an organic lithium salt and an inorganic lithium salt.

4. The composite electrolyte according to claim 3, characterized in that The self-healing monomer includes one or more of boron trioxide, boric acid, 1,4-phenyldiboric acid, 4,4'-biphenyldiboric acid, 2,7-pyrene diboric acid, and 3,5-dimethoxyphenylboric acid; and / or The degree of polymerization of the oligomer is 2 to 10; and / or The oligomer comprises a hydroxyl-terminated oligomer, and the hydroxyl-terminated oligomer comprises one or more of polyethylene glycol, polytetramethylene glycol, polycaprolactone glycol, polypropylene glycol, and a hydroxyl polyethylene glycol polylactic acid diblock copolymer; and / or The molar ratio of the self-healing monomer to the oligomer is (0.5-2):3; and / or The organic lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium difluorooxalatoborate, and lithium bis(oxalatoborate); and / or The inorganic lithium salt includes one or more of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium difluorophosphate.

5. The composite electrolyte according to claim 1, characterized in that The metal organic framework material comprises metal ions and organic ligands; and / or The metal organic framework material is a defective metal organic framework material; and / or The defective metal organic framework material contains a regulator.

6. The composite electrolyte according to claim 5, characterized in that The metal ions include one or more of magnesium ions, copper ions, nickel ions, cobalt ions, zinc ions, aluminum ions, zirconium ions and chromium ions; and / or The organic ligand includes one or more of an aromatic acid ligand and a heteroaromatic ligand; the aromatic acid ligand contains at least two coordination functional groups, the aromatic acid ligand includes an aromatic dicarboxylic acid ligand, and the aromatic dicarboxylic acid ligand includes one or more of 1,4-benzenedicarboxylic acid, 1,3,5-benzenetricarboxylic acid, 1,4-biphenyldicarboxylic acid, and 4,4'-dihydroxybiphenyl-3,3'-dicarboxylic acid; the heteroatom in the heteroaromatic ligand includes a nitrogen atom, and the heteroaromatic ligand includes one or more of imidazole, 1-methylimidazole, and 2-methylimidazole; and / or The molar ratio of the metal ion to the organic ligand is (1.5-3):1; and / or The regulator includes a monocarboxylic acid compound; the monocarboxylic acid compound includes one or more of formic acid, acetic acid, propionic acid, butyric acid, valeric acid, hexanoic acid, heptanoic acid, trifluoroacetic acid, and benzoic acid.

7. A method for preparing a composite electrolyte, characterized in that: The method comprises the following steps: Providing a metal organic framework material, a self-healing precursor and a lithium salt, and mixing them to obtain a mixture; The mixture is heated to make the self-repairing precursor react to form a self-repairing polymer material containing dynamic Lewis acid bonds, thereby obtaining a composite electrolyte.

8. The preparation method according to claim 7, characterized in that: The mass ratio of the metal organic framework material, the self-healing precursor and the lithium salt is (3-20): (75-96): (1-5); and / or The temperature of heating the mixture is 60° C. to 120° C. and the time is 5 h to 24 h.

9. The preparation method according to claim 7, characterized in that: The preparation method of the metal organic framework material comprises: providing metal salts, organic ligands and solvents; The metal salt, the organic ligand and the solvent are mixed and reacted to obtain a metal organic framework material.

10. The preparation method according to claim 9, characterized in that: The metal salt comprises one or more of magnesium salt, copper salt, nickel salt, cobalt salt, zinc salt, aluminum salt, zirconium salt and chromium salt; and / or The anions in the metal salt include one or more of nitrate ions, sulfate ions, halogen ions, and acetate ions; and / or The molar ratio of the metal salt to the organic ligand is (1.5-3):1; and / or The solvent includes a polar solvent; the polar solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, methanol, ethanol, propanol, ethylene glycol, and acetone; and / or After the metal salt, the organic ligand and the solvent are mixed, the molar concentration of the metal salt is 0.1 mol / L to 0.5 mol / L; and / or After the metal salt, the organic ligand and the solvent are mixed, the molar concentration of the organic ligand is 0.05 mol / L to 0.3 mol / L; and / or The temperature for the reaction of the metal salt, the organic ligand and the solvent is 30° C. to 150° C.; the reaction time is 12 h to 48 h; and / or The metal organic framework material is a defective metal organic framework material, and the mixing of the metal salt, the organic ligand and the solvent further comprises: adding a regulator.

11. The preparation method according to claim 9, characterized in that: After the metal salt, the organic ligand and the solvent react, one or more of centrifugation, extraction and vacuum activation treatments are performed in sequence; wherein, The centrifugal solvent of the centrifugation includes a polar solvent, and the polar solvent includes one or more of N,N-dimethylformamide, methanol, ethanol, dimethyl sulfoxide, propanol, and ethylene glycol; the centrifugal speed is 5000rpm to 8000rpm; the centrifugal frequency is 5min / time to 8min / time, and the number of times is 3 to 5 times; and / or The extraction solvent includes a polar solvent, and the polar solvent includes one or more of methanol and ethanol; the extraction temperature is 100° C. to 150° C.; the extraction time is 1 day to 5 days; and / or The temperature of the vacuum activation is 70° C. to 300° C., and the time is 1 h to 24 h.

12. An electrolyte membrane, characterized in that: The material of the electrolyte film includes the composite electrolyte according to any one of claims 1 to 6, or includes the composite electrolyte prepared by the preparation method according to any one of claims 7 to 11.

13. A battery, characterized in that: It comprises a positive electrode, a negative electrode and an electrolyte film located between the positive electrode and the negative electrode, wherein the material of the electrolyte film comprises the composite electrolyte as described in any one of claims 1 to 6, or comprises a composite electrolyte prepared by the preparation method as described in any one of claims 7 to 11.